(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The paper seeks to develop and validate a comprehensive framework for measuring entrepreneurial capabilities across business contexts and organisational scales. Design/Methodology/Approach: Cross-sectional research involved 254 owners of SMEs from Sukuma and Chagga ethnic groups. The snowball sampling procedure was first adopted to obtain the list of the Sukuma and Chagga owners of SMEs. Then, proportionate stratified sampling was adopted to select a final subject. Data were gathered using a questionnaire, where factor analysis was performed to reduce the number of predictors. A logit model was thereafter performed to establish the influence of predictors on entrepreneurial capabilities. Further, using the Whitney U test, a comparison of ways to preserve drivers of entrepreneurial capabilities between the Sukuma and Chagga owners of SMEs was performed. Findings: Factor analysis reduced 52 predictors into six variables, which were further subjected to a logit model. The findings indicated that social factors, beliefs, norms, attitudes, and values were statistically significant while perception was insignificant. The difference in ways to preserve socio-cultural determinants between the Sukuma and Chagga was statistically significant, and the effect size was very high. Research Limitation: The research was limited by the use of the logit model and the Man Whitney U test. Other econometric models, such as multiple linear regression, Tobit, Probit, etc., should be considered in the future. Practical implications: The approach will help researchers and academicians to quantify socio-cultural studies and perform factor analysis step by step to reduce variables for further analysis using econometric models. Social Implication: This approach will have social implications. Social scientists will be able to forecast the effect of social variables on certain variables under study, thus enabling the setting of priorities during intervention. Originality: This research fills a significant gap in entrepreneurship literature by providing a validated, comprehensive framework for measuring entrepreneurial capabilities across different contexts and scales.